Evaluation of antioxidant content in introductions of cherry tomato (solanum spp.) (2012)
The greatest genetic diversity of tomato (Solanum lycopersicum L.) is found in wild species, with variability in fruit quality characteristics such as flavor, aroma, color, and content of lycopene and β-carotene. The aim of this study was to determine the content of antioxidants (lycopene, β-carotene and vitamin C) in cherry tomato fruits of 30 wild introductions from the Germplasm Bank of the National University of Colombia in Palmira. The field study was conducted at Montelindo farm, property of the University of Caldas, with an average temperature of 22.8 °C, at 1010 masl, 2200 mm of annual precipitation and relative humidity of 76%. The experimental design used was a rectangular lattice, with 30 treatments (introductions) and a commercial control (Sweet million) in four replicates per treatment and five plants in each one as experimental unit. The evaluated variables were lycopene, β-carotene, vitamin C and acidity of the fruit, which were determined by spectrophotometry and titration by color change and pH. Additionally, fruit production of the introductions was assessed. Data were analyzed using ANOVA and Duncan mean test by using SAS software (SAS Institute, Cary NC). Finally, we applied a weighted selection index based on the variables lycopene, β-carotene and vitamin C, applying a selection pressure of 17%. Significant differences (P